Perfecting Approaches to Personnel Recruitment in the Hospitality Industry - Nikolskaya, Elena; Zakharova, Elena; Avilova, Natalia; Konovalova, Alla; Dmitrieva, Olga (Anais Brasileiros de Estudos Turísticos, 2022)
The purpose of the article is to develop a recommendation system for hospitality enterprises using non-traditional forms of recruitment. The dynamism of changes in the environment is found to necessitate the use of innovative approaches based on the real needs and opportunities of modern hospitality industry enterprises. It is confirmed that the effectiveness of personnel recruitment depends on the mastery of up-to-date methods. It is established that implementing the totality of the proposed modern human resource management technologies will contribute to increased personnel productivity and efficiency of hotel enterprises. The introduction and implementation of innovative technologies of personnel management are found to bring changes to other resource areas – in the nature of the hotel product, in the way relationships with the key customers are constructed, and in the economy of the hotel enterprise as a whole in a digitalized environment.